Pindar’s Pythian 12: When Mortals Triumph, the Gods Weep - Papadimitropoulos, Loukas (Polskie Towarzystwo Filologiczne, 2022)
In this paper I maintain that the adjective δυσπενθέϊ in line 10 of Pindar’s Pythian 12 possibly alludes to Perseus’ future murderer Megapenthes, suggesting thus that triumph might eventually lead to disaster, an idea that the Theban poet probably borrowed from the Odyssey. This allusion better explains certain parts of the poem and defines what the laudandus’ instrument, the aulos, has come to symbolise. Nevertheless, Pindar does not confine himself to pointing out the dangers underlying any great achievement, but also proposes, in an implicit way, his own solution to this problem, namely the harmonious integration of the gifted individual into his civic setting, which has the capacity to serve as a protective confinement for him.